Exploring the effects of hypoxia and reoxygenation time on hepatocyte apoptosis and inflammation. - Xinlu Xu; Tanfang Zhou; Alimu Tulahong; Rexiati Ruze; Yingmei Shao (PLoS ONE)
Hepatic Ischemia-Reperfusion Injury (HIRI) is an unavoidable pathological process during liver surgeries such as liver transplantation and hepatic resection, which involves a complex set of molecular and cellular mechanisms. The mechanisms of HIRI may involve a variety of biological processes in which inflammation and apoptosis play a central role. Therefore, it is crucial to deeply investigate the effects of different hypoxia and reoxygenation times on the construction of an in vitro model of hepatic ischemia-reperfusion injury. The human normal liver cell line HL-7702 IRI model was constructed by hypoxia chamber, and the inflammation and apoptosis focal levels of cells were detected by enzyme-linked immunosorbent assay, western blot and quantitative reverse transcription polymerase chain reaction. When 12-hour reoxygenation time was fixed, the inflammation and apoptosis indexes of HIRI model increased with the prolongation of hypoxia time (6, 12 and 24 hours). These indices reached highest level in the model group of 24-hour fixed hypoxia and 12-hour reoxygenation. Inflammation and apoptosis indices were significantly higher in the model group of 24-hours fixed hypoxia and 12-hours reoxygenation than in the group of 6 and 24 hours of reoxygenation. Taken together, the findings from this research demonstrated that during hypoxia phase, cells exhibited a clear time-dependent response of inflammation and cell death; on the contrary, during the reoxygenation phase, the cellular damage was not monotonically incremental, but showed an inverted U-shaped dynamic pattern. The present study reveals in depth the dynamic changes of cellular responses under hypoxia and reoxygenation conditions, providing us with an important theoretical basis to guide the selection and optimization of in vitro experimental models.